A Proposition About Common Reporting Standard (CRS) As Evidence: A Tax Criminal Procedure Law Perspective in Indonesia - Prasetyo, Erwan B. (Journal of Posthumanism, 2025)
The globalization of the economy and advances in information technology have facilitated international economic activities, which, while fostering growth, also increase the potential for economic crimes, particularly in taxation. This study explores the proposition of using CRS as evidence in the taxation of criminal offenses in Indonesia. The primary objective is to evaluate whether CRS data can serve as valid evidence in tax-related criminal cases. Employing a qualitative research method, this study analyzes legal frameworks and applies the constructivist paradigm to explore the relevance and applicability of CRS data in criminal tax proceedings. The results indicate that CRS can indeed be used as evidence, provided that its authenticity and content are verified. Key factors for its admissibility include the nature of the CRS, the accuracy of its content, and its proper implementation. In conclusion, CRS serves as a valuable tool in enhancing tax transparency and can be pivotal in prosecuting tax offenses, though its legal standing requires further refinement, particularly in international legal agreements. This research suggests that CRS should be formally recognized as documentary evidence in the context of Indonesian tax law.